2012
DOI: 10.1007/s10483-012-1548-6
|View full text |Cite
|
Sign up to set email alerts
|

New exact penalty function for solving constrained finite min-max problems

Abstract: This paper introduces a new exact and smooth penalty function to tackle constrained min-max problems. By using this new penalty function and adding just one extra variable, a constrained min-max problem is transformed into an unconstrained optimization one. It is proved that, under certain reasonable assumptions and when the penalty parameter is sufficiently large, the minimizer of this unconstrained optimization problem is equivalent to the minimizer of the original constrained one. Numerical results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Let us also obtains an interesting property of cluster points of a minimizing sequence constructed with the use of a parametric penalty function (i.e. a sequence satisfying (35)) in the case when this penalty function is not exact. Proposition 3.22.…”
Section: The Following Inequalities Hold Truementioning
confidence: 99%
See 1 more Smart Citation
“…Let us also obtains an interesting property of cluster points of a minimizing sequence constructed with the use of a parametric penalty function (i.e. a sequence satisfying (35)) in the case when this penalty function is not exact. Proposition 3.22.…”
Section: The Following Inequalities Hold Truementioning
confidence: 99%
“…Throughout this article, we refer to the penalty function proposed in [23] as a singular exact penalty function, since one achieves smoothness of this exact penalty function via the introduction of a singular term into the definition of this function. Recently, singular exact penalty functions have attracted a lot of attention of researchers [6,14,15,44], and were successfully applied to various constrained optimization problems [25,27,31,32,35,51,52]. It should be noted that the main feature of both smoothing approximations of exact penalty functions and singular exact penalty functions is the fact that they depend on some additional parameters apart from the penalty parameter.…”
Section: Introductionmentioning
confidence: 99%
“…h GOPF algorithm provides an alternative method to solve (P1). In GOPF algorithm, it does not need to increase the parameter M to 1, which differs from other penalty function methods [17][18][19][20]. Theorem 2.3 is obviously of great theoretical interest, however, if we use standard optimization methods to solve the sequences of problem (PM) we may possibly find local solutions of problem (PM).…”
Section: Proofmentioning
confidence: 99%
“…Recently, for dealing with finite constrained minimax problems, Obasanjo et al [19] presented a primal-dual interior-point method to solve the equivalent problem (P2). Ma et al [20] introduced a new exact and smooth penalty function to tackle minimax problems with equality constraints, in which the penalty parameter needed to be increased gradually to infinity. Based on the equivalent reformulation (P2) and a novel continuously differentiable exact objective penalty function, we propose a penalty function method to solve the minimax problem (P1) by taking a finite penalty parameter.…”
Section: Introductionmentioning
confidence: 99%
“…extended or parametric penalty function) was introduced by Huyer and Neumaier [22] in 2003. This penalty function was generalized and, later on, applied to various optimization problems in [1,35,24,30,26,23,25,31,39,13]. In [12], it was shown that Huyer and Neumaier's extended penalty function is exact if and only if the standard nonsmooth penalty function is exact, and some relations between the least exact penalty parameters of these functions were obtained.…”
Section: Introductionmentioning
confidence: 99%